De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith-Magenis syndrome. - Vetrini, Francesco; McKee, Shane; Rosenfeld, Jill A; Suri, Mohnish; Lewis, Andrea M; Nugent, Kimberly Margaret; Roeder, Elizabeth; Littlejohn, Rebecca O; Holder, Sue; Zhu, Wenmiao; Alaimo, Joseph T; Graham, Brett; et al. (Genome Med, 2019)
BACKGROUND: Neurodevelopmental disorders are genetically and phenotypically heterogeneous encompassing developmental delay (DD), intellectual disability (ID), autism spectrum disorders (ASDs), structural brain abnormalities, and neurological manifestations with variants in a large number of genes (hundreds) associated. To date, a few de novo mutations potentially disrupting TCF20 function in patients with ID, ASD, and hypotonia have been reported. TCF20 encodes a transcriptional co-regulator structurally related to RAI1, the dosage-sensitive gene responsible for Smith-Magenis syndrome (deletion/haploinsufficiency) and Potocki-Lupski syndrome (duplication/triplosensitivity). METHODS: Genome-wide analyses by exome sequencing (ES) and chromosomal microarray analysis (CMA) identified individuals with heterozygous, likely damaging, loss-of-function alleles in TCF20. We implemented further molecular and clinical analyses to determine the inheritance of the pathogenic variant alleles and studied the spectrum of phenotypes. RESULTS: We report 25 unique inactivating single nucleotide variants/indels (1 missense, 1 canonical splice-site variant, 18 frameshift, and 5 nonsense) and 4 deletions of TCF20. The pathogenic variants were detected in 32 patients and 4 affected parents from 31 unrelated families. Among cases with available parental samples, the variants were de novo in 20 instances and inherited from 4 symptomatic parents in 5, including in one set of monozygotic twins. Two pathogenic loss-of-function variants were recurrent in unrelated families. Patients presented with a phenotype characterized by developmental delay, intellectual disability, hypotonia, variable dysmorphic features, movement disorders, and sleep disturbances. CONCLUSIONS: TCF20 pathogenic variants are associated with a novel syndrome manifesting clinical characteristics similar to those observed in Smith-Magenis syndrome. Together with previously described cases, the clinical entity of TCF20-associated neurodevelopmental disorders (TAND) emerges from a genotype-driven perspective.
Keywords: Adolescent; Child; Child, Preschool; Craniofacial Abnormalities; Developmental Disabilities; Female; Humans; INDEL Mutation; Infant; Intellectual Disability; Male; Muscle Hypotonia; Smith-Magenis Syndrome; Transcription Factors; Young Adult

Truncating Variants in NAA15 Are Associated with Variable Levels of Intellectual Disability, Autism Spectrum Disorder, and Congenital Anomalies. - Cheng, Hanyin; Dharmadhikari, Avinash V; Varland, Sylvia; Ma, Ning; Domingo, Deepti; Kleyner, Robert; Rope, Alan F; Yoon, Margaret; Stray-Pedersen, Asbjørg; Posey, Jennifer E; Crews, Sarah R; Eldomery, Mohammad K; et al. (Am J Hum Genet, 2018)
N-alpha-acetylation is a common co-translational protein modification that is essential for normal cell function in humans. We previously identified the genetic basis of an X-linked infantile lethal Mendelian disorder involving a c.109T>C (p.Ser37Pro) missense variant in NAA10, which encodes the catalytic subunit of the N-terminal acetyltransferase A (NatA) complex. The auxiliary subunit of the NatA complex, NAA15, is the dimeric binding partner for NAA10. Through a genotype-first approach with whole-exome or genome sequencing (WES/WGS) and targeted sequencing analysis, we identified and phenotypically characterized 38 individuals from 33 unrelated families with 25 different de novo or inherited, dominantly acting likely gene disrupting (LGD) variants in NAA15. Clinical features of affected individuals with LGD variants in NAA15 include variable levels of intellectual disability, delayed speech and motor milestones, and autism spectrum disorder. Additionally, mild craniofacial dysmorphology, congenital cardiac anomalies, and seizures are present in some subjects. RNA analysis in cell lines from two individuals showed degradation of the transcripts with LGD variants, probably as a result of nonsense-mediated decay. Functional assays in yeast confirmed a deleterious effect for two of the LGD variants in NAA15. Further supporting a mechanism of haploinsufficiency, individuals with copy-number variant (CNV) deletions involving NAA15 and surrounding genes can present with mild intellectual disability, mild dysmorphic features, motor delays, and decreased growth. We propose that defects in NatA-mediated N-terminal acetylation (NTA) lead to variable levels of neurodevelopmental disorders in humans, supporting the importance of the NatA complex in normal human development.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Autism Spectrum Disorder; Cell Line; Child; Exons; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Genetic Variation; Humans; Intellectual Disability; Male; Middle Aged; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Pedigree; Phenotype; RNA, Messenger; Saccharomyces cerevisiae

De Novo Disruption of the Proteasome Regulatory Subunit PSMD12 Causes a Syndromic Neurodevelopmental Disorder. - Küry, Sébastien; Besnard, Thomas; Ebstein, Frédéric; Khan, Tahir N; Gambin, Tomasz; Douglas, Jessica; Bacino, Carlos A; Craigen, William J; Sanders, Stephan J; Lehmann, Andrea; Latypova, Xénia; Khan, Kamal; et al. (Am J Hum Genet, 2017)
Degradation of proteins by the ubiquitin-proteasome system (UPS) is an essential biological process in the development of eukaryotic organisms. Dysregulation of this mechanism leads to numerous human neurodegenerative or neurodevelopmental disorders. Through a multi-center collaboration, we identified six de novo genomic deletions and four de novo point mutations involving PSMD12, encoding the non-ATPase subunit PSMD12 (aka RPN5) of the 19S regulator of 26S proteasome complex, in unrelated individuals with intellectual disability, congenital malformations, ophthalmologic anomalies, feeding difficulties, deafness, and subtle dysmorphic facial features. We observed reduced PSMD12 levels and an accumulation of ubiquitinated proteins without any impairment of proteasome catalytic activity. Our PSMD12 loss-of-function zebrafish CRISPR/Cas9 model exhibited microcephaly, decreased convolution of the renal tubules, and abnormal craniofacial morphology. Our data support the biological importance of PSMD12 as a scaffolding subunit in proteasome function during development and neurogenesis in particular; they enable the definition of a neurodevelopmental disorder due to PSMD12 variants, expanding the phenotypic spectrum of UPS-dependent disorders.
Keywords: Adolescent; Animals; Child; Child, Preschool; Disease Models, Animal; DNA Copy Number Variations; Down-Regulation; Female; Gene Deletion; Humans; Infant; Intellectual Disability; Male; Microcephaly; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Proteasome Endopeptidase Complex; Zebrafish

Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features. - Zhang, Jing; Gambin, Tomasz; Yuan, Bo; Szafranski, Przemyslaw; Rosenfeld, Jill A; Balwi, Mohammed Al; Alswaid, Abdulrahman; Al-Gazali, Lihadh; Shamsi, Aisha M Al; Komara, Makanko; Ali, Bassam R; Roeder, Elizabeth; et al. (Hum Genet, 2017)
Impairment of ubiquitin-proteasome system activity involving ubiquitin ligase genes UBE3A, UBE3B, and HUWE1 and deubiquitinating enzyme genes USP7 and USP9X has been reported in patients with neurodevelopmental delays. To date, only a handful of single-nucleotide variants (SNVs) and copy-number variants (CNVs) involving TRIP12, encoding a member of the HECT domain E3 ubiquitin ligases family on chromosome 2q36.3 have been reported. Using chromosomal microarray analysis and whole-exome sequencing (WES), we have identified, respectively, five deletion CNVs and four inactivating SNVs (two frameshifts, one missense, and one splicing) in TRIP12. Seven of these variants were found to be de novo; parental studies could not be completed in two families. Quantitative PCR analyses of the splicing mutation showed a dramatically decreased level of TRIP12 mRNA in the proband compared to the family controls, indicating a loss-of-function mechanism. The shared clinical features include intellectual disability with or without autistic spectrum disorders, speech delay, and facial dysmorphism. Our findings demonstrate that E3 ubiquitin ligase TRIP12 plays an important role in nervous system development and function. The nine presented pathogenic variants further document that TRIP12 haploinsufficiency causes a childhood-onset neurodevelopmental disorder. Finally, our data enable expansion of the phenotypic spectrum of ubiquitin-proteasome dependent disorders.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Cohort Studies; DNA Copy Number Variations; Facies; Female; Haploinsufficiency; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Ubiquitin-Protein Ligases

Phenotypic and molecular characterisation of CDK13-related congenital heart defects, dysmorphic facial features and intellectual developmental disorders. - Bostwick, Bret L; McLean, Scott; Posey, Jennifer E; Streff, Haley E; Gripp, Karen W; Blesson, Alyssa; Powell-Hamilton, Nina; Tusi, Jessica; Stevenson, David A; Farrelly, Ellyn; Hudgins, Louanne; Yang, Yaping; et al. (Genome Med, 2017)
BACKGROUND: De novo missense variants in CDK13 have been described as the cause of syndromic congenital heart defects in seven individuals ascertained from a large congenital cardiovascular malformations cohort. We aimed to further define the phenotypic and molecular spectrum of this newly described disorder. METHODS: To minimise ascertainment bias, we recruited nine additional individuals with CDK13 pathogenic variants from clinical and research exome laboratory sequencing cohorts. Each individual underwent dysmorphology exam and comprehensive medical history review. RESULTS: We demonstrate greater than expected phenotypic heterogeneity, including 33% (3/9) of individuals without structural heart disease on echocardiogram. There was a high penetrance for a unique constellation of facial dysmorphism and global developmental delay, as well as less frequently seen renal and sacral anomalies. Two individuals had novel CDK13 variants (p.Asn842Asp, p.Lys734Glu), while the remaining seven unrelated individuals had a recurrent, previously published p.Asn842Ser variant. Summary of all variants published to date demonstrates apparent restriction of pathogenic variants to the protein kinase domain with clustering in the ATP and magnesium binding sites. CONCLUSIONS: Here we provide detailed phenotypic and molecular characterisation of individuals with pathogenic variants in CDK13 and propose management guidelines based upon the estimated prevalence of anomalies identified.
Keywords: Adolescent; Adult; CDC2 Protein Kinase; Child; Child, Preschool; Face; Female; Heart Defects, Congenital; Humans; Infant; Intellectual Disability; Male; Mutation; Phenotype; Syndrome

Germline De Novo Mutations in GNB1 Cause Severe Neurodevelopmental Disability, Hypotonia, and Seizures. - Petrovski, Slavé; Küry, Sébastien; Myers, Candace T; Anyane-Yeboa, Kwame; Cogné, Benjamin; Bialer, Martin; Xia, Fan; Hemati, Parisa; Riviello, James; Mehaffey, Michele; Besnard, Thomas; Becraft, Emily; et al. (Am J Hum Genet, 2016)
Whole-exome sequencing of 13 individuals with developmental delay commonly accompanied by abnormal muscle tone and seizures identified de novo missense mutations enriched within a sub-region of GNB1, a gene encoding the guanine nucleotide-binding protein subunit beta-1, Gβ. These 13 individuals were identified among a base of 5,855 individuals recruited for various undiagnosed genetic disorders. The probability of observing 13 or more de novo mutations by chance among 5,855 individuals is very low (p = 7.1 × 10(-21)), implicating GNB1 as a genome-wide-significant disease-associated gene. The majority of these 13 mutations affect known Gβ binding sites, which suggests that a likely disease mechanism is through the disruption of the protein interface required for Gα-Gβγ interaction (resulting in a constitutively active Gβγ) or through the disruption of residues relevant for interaction between Gβγ and certain downstream effectors (resulting in reduced interaction with the effectors). Strikingly, 8 of the 13 individuals recruited here for a neurodevelopmental disorder have a germline de novo GNB1 mutation that overlaps a set of five recurrent somatic tumor mutations for which recent functional studies demonstrated a gain-of-function effect due to constitutive activation of G protein downstream signaling cascades for some of the affected residues.
Keywords: Adolescent; Adult; Child; Child, Preschool; Developmental Disabilities; Exome; Female; Germ-Line Mutation; GTP-Binding Protein beta Subunits; Humans; Infant; Intellectual Disability; Male; Muscle Hypotonia; Phenotype; Protein Conformation; Seizures; Signal Transduction; Young Adult

POGZ truncating alleles cause syndromic intellectual disability. - White, Janson; Beck, Christine R; Harel, Tamar; Posey, Jennifer E; Jhangiani, Shalini N; Tang, Sha; Farwell, Kelly D; Powis, Zöe; Mendelsohn, Nancy J; Baker, Janice A; Pollack, Lynda; Mason, Kati J; et al. (Genome Med, 2016)
BACKGROUND: Large-scale cohort-based whole exome sequencing of individuals with neurodevelopmental disorders (NDDs) has identified numerous novel candidate disease genes; however, detailed phenotypic information is often lacking in such studies. De novo mutations in pogo transposable element with zinc finger domain (POGZ) have been identified in six independent and diverse cohorts of individuals with NDDs ranging from autism spectrum disorder to developmental delay. METHODS: Whole exome sequencing was performed on five unrelated individuals. Sanger sequencing was used to validate variants and segregate mutations with the phenotype in available family members. RESULTS: We identified heterozygous truncating mutations in POGZ in five unrelated individuals, which were confirmed to be de novo or not present in available parental samples. Careful review of the phenotypes revealed shared features that included developmental delay, intellectual disability, hypotonia, behavioral abnormalities, and similar facial characteristics. Variable features included short stature, microcephaly, strabismus and hearing loss. CONCLUSIONS: While POGZ has been associated with neurodevelopmental disorders in large cohort studies, our data suggest that loss of function variants in POGZ lead to an identifiable syndrome of NDD with specific phenotypic traits. This study exemplifies the era of human reverse clinical genomics ushered in by large disease-directed cohort studies; first defining a new syndrome molecularly and, only subsequently, phenotypically.
Keywords: Adolescent; Adult; Alleles; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Sequence Analysis, DNA; Transposases

De novo truncating mutations in AHDC1 in individuals with syndromic expressive language delay, hypotonia, and sleep apnea. - Xia, Fan; Bainbridge, Matthew N; Tan, Tiong Yang; Wangler, Michael F; Scheuerle, Angela E; Zackai, Elaine H; Harr, Margaret H; Sutton, V Reid; Nalam, Roopa L; Zhu, Wenmiao; Nash, Margot; Ryan, Monique M; et al. (Am J Hum Genet, 2014)
Clinical whole-exome sequencing (WES) for identification of mutations leading to Mendelian disease has been offered to the medical community since 2011. Clinically undiagnosed neurological disorders are the most frequent basis for test referral, and currently, approximately 25% of such cases are diagnosed at the molecular level. To date, there are approximately 4,000 "known" disease-associated loci, and many are associated with striking dysmorphic features, making genotype-phenotype correlations relatively straightforward. A significant fraction of cases, however, lack characteristic dysmorphism or clinical pathognomonic traits and are dependent upon molecular tests for definitive diagnoses. Further, many molecular diagnoses are guided by recent gene-disease association discoveries. Hence, there is a critical interplay between clinical testing and research leading to gene-disease association discovery. Here, we describe four probands, all of whom presented with hypotonia, intellectual disability, global developmental delay, and mildly dysmorphic facial features. Three of the four also had sleep apnea. Each was a simplex case without a remarkable family history. Using WES, we identified AHDC1 de novo truncating mutations that most likely cause this genetic syndrome.
Keywords: Child; Child, Preschool; DNA-Binding Proteins; Exome; Female; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Muscle Hypotonia; Mutation; Sleep Apnea Syndromes; Syndrome